Iliac artery endofibrosis in high-performance athletes - Peach, G.; Hinchliffe, R. J. (ASPETAR Sports Medicine Journal, 2015)
Exercise-induced leg pain is a very common symptom and affects a huge variety of patients. It can be caused by a wide range of pathologies and affect many different joints or muscle groups, but when reported by high-performance athletes it can sometimes lead to diagnostic difficulty. This group is typically involved in high-intensity or high-impact sports where physical injury is common and pain is often attributed to musculoskeletal causes. It is only when symptoms fail to resolve despite standard therapy regimens that other potential causes are sought. This article focuses on a frequently overlooked cause of leg pain in young athletes - iliac artery endofibrosis (IAE).